MANAGEMENT PRACTICES AND ISLAMIC ENTREPRENEURIAL LEADERSHIP: ORGANIZATIONAL EFFECTIVENESS IN ISLAMIC HIGHER EDUCATION - Heru Setiawan; Mohd Kasturi Nor bin Abd Aziz; Irwan Fathurrochman; Zulhimma Zulhimma; Mona Novita (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
This study aimed to investigate the role of management practices and Islamic Entrepreneurial Leadership in enhancing organizational effectiveness of Islamic educational institutions in Indonesia, with Islamic work ethic as an additional predictor variable. The research employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SEMinR package. Data were collected through structured questionnaires distributed to 250 lecturers at Perguruan Tinggi Keagamaan Islam Swasta (PTKIS) across Indonesia, yielding 218 valid responses. The measurement model demonstrated excellent reliability (Cronbach’s Alpha > 0.86) and validity (AVE > 0.71) for all constructs. The structural model revealed that Islamic work ethic (β = 0.756, t = 32.575) and Islamic Entrepreneurial Leadership (β = 0.744, t = 24.473) significantly and positively influence organizational effectiveness, while management practices exhibited a significant negative effect (β = -0.508, t = -24.082). The model explained 99.25% of the variance in organizational effectiveness (R² = 0.9925). These findings suggest that Islamic educational institutions should prioritize cultivating Islamic work ethic values and developing Islamic Entrepreneurial Leadership capacity, while critically re-evaluating existing management practices that may be overly bureaucratic or misaligned with institutional goals. This study contributes to the limited empirical evidence on organizational effectiveness in the unique context of Islamic higher education institutions in Indonesia